Mouthpart Morphology and Wild Diet of Zoeae of the Ghost Shrimp, Nihonotrypaea harmandi (Decapoda: Axiidea: Callianassidae). Issue 3 (1st May 2014) - Somiya, Rei; Suzuki, Toshikazu; Tamaki, Akio
Abstract: To infer diet and feeding mode of zoea of Nihonotrypaea harmandi (Bouvier, 1901 ), fine functional morphology of the mouthparts and composition of undigested remnants of ingested prey organisms contained in the gut were investigated. A mesh-like structure was observed for the coxal and basal endites of the maxilla, which would be suitable for filter feeding. The mandible edge is equipped with many fine processes and resembles the mandible edge of herbivorous copepod. Abrasion of the incisor processes, which must be caused by frequent mastication of planktonic diatoms, was recognized within a molting interval. Furthermore, diatom frustules and their crushed fragments were frequently observed in the gut contents. These observations indicate that zoea of N. harmandi may regularly feed on phytoplankton, especially diatoms.